Optimal Design of Structures under Impact Loading - Uwe Schramm; Walter D. Pilkey (Shock and Vibration)
In the design process structural optimization is a useful tool to reach design decisions. The impact behavior of structures is important for many designs, such as for automobiles. This article reviews methodology for the optimization of structures under impact loading. The optimization problem is to minimize the structural mass with constraints on the transient dynamic response of the structure. The structural behavior is nonlinear dynamic. Optimization is performed using the approximation concept. Design sensitivity analysis for transient response is treated.